Dampak Perbedaan Akses Ruang Terbuka dan Fungsi Kognisi terhadap Aktivitas Fisik Siswa SMP di Masa Digital - Sandi Permana; Alit Rahmat; Helmy Firmansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Physical activity among junior high school students tends to decline in the digital era due to increasing gadget use and sedentary behavior. Beyond digitalization, access to public open space and cognitive function also shape students' movement habits. This study aimed to describe the level of physical activity and cognitive function among junior high school students, to examine differences in physical activity based on open space access, and to test the effect of open space access and cognitive function on students' physical activity. A quantitative ex post facto approach, comparative and associative in nature, was employed. The sample consisted of 234 seventh-, eighth-, and ninth-grade students selected through cluster sampling from SMPN 3 Lembang (high open space access) and SMPN 2 Baleendah (low open space access). Data were collected using Likert-scale questionnaires and analyzed using the Mann-Whitney U test, simple linear regression, and multiple linear regression. Results showed that students' physical activity (mean = 45.55) and cognitive function (mean = 46.21) were in the moderate category. A significant difference in physical activity was found based on open space access (Mann-Whitney U = 5118.500; Sig. = 0.002), with students in high-access areas showing higher physical activity. Cognitive function significantly affected physical activity (R² = 0.170; Sig. = 0.000), and together with open space access simultaneously explained 21.3% of the variance in physical activity (F = 31.176; Sig. = 0.000), with cognitive function (Beta = 0.342) contributing more than open space access (Beta = 0.217). These findings underline the importance of combining environmental interventions with strengthening students' self-regulation to promote an active lifestyle in the digital era. Keywords: Open Space Access, Physical Activity, Digital Era, Cognitive Function, Junior High School Students